2000
DOI: 10.1161/01.atv.20.6.1521
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic Acid Induces Delayed Protection in the Rat Heart

Abstract: Abstract-Classic ischemic preconditioning transiently (30 to 120 minutes) protects the myocardium against subsequent lethal ischemia/reperfusion injury. After dissipation of this acute protection, a second window of protection (SWOP) appears 12 to 24 hours later; this SWOP lasts up to 3 days. Several triggers induce a SWOP, including brief repetitive cycles of coronary artery occlusion, rapid ventricular pacing, stimulation of adenosine A 1 receptors, and administration of wall fragments of Gram-negative bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 64 publications
1
13
1
Order By: Relevance
“…For example, hearts isolated from rats pretreated with a low dose of LPS (0.5 mg/kg) 24 h before had a better preserved myocardial function after I/R compared with the saline-treated control hearts (18,105). Similar cardiac protection in LPS-treated animals was observed in vivo and in different animal models of I/R injury, such as rabbit (13,99), rat (18,88,106,138,155,166,167), and mice (48). The cardioprotective effect of LPS usually occurs between 12-24 h after the administration of LPS and is abolished by cycloheximide (106), suggesting a mechanism involving the de novo synthesis of cardioprotective proteins.…”
Section: Lps Preconditioning Against I/r Injurymentioning
confidence: 63%
See 2 more Smart Citations
“…For example, hearts isolated from rats pretreated with a low dose of LPS (0.5 mg/kg) 24 h before had a better preserved myocardial function after I/R compared with the saline-treated control hearts (18,105). Similar cardiac protection in LPS-treated animals was observed in vivo and in different animal models of I/R injury, such as rabbit (13,99), rat (18,88,106,138,155,166,167), and mice (48). The cardioprotective effect of LPS usually occurs between 12-24 h after the administration of LPS and is abolished by cycloheximide (106), suggesting a mechanism involving the de novo synthesis of cardioprotective proteins.…”
Section: Lps Preconditioning Against I/r Injurymentioning
confidence: 63%
“…In animal models of I/R injury (13,18,48,88,89,99,106,138,155,166,167), in both in vivo (13,48,99,138,155,166,167) and ex vivo (18,88,106), a prior systemic administration of a sublethal dose of LPS reduces subsequent MI and improved cardiac functions. For example, hearts isolated from rats pretreated with a low dose of LPS (0.5 mg/kg) 24 h before had a better preserved myocardial function after I/R compared with the saline-treated control hearts (18,105).…”
Section: Lps Preconditioning Against I/r Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic preconditioning is a well-described cardioprotective strategy in which brief exposure to ischemia remarkably enhances the ability of heart to withstand a subsequent ischemia/reperfusion injury Churchill et al 2010). Numerous studies also have shown that gram-negative bacterial LPS induced myocardial protection (Zacharowski et al 2000;Meng et al 1997). Specifically, pretreatment of rats with LPS for 24 h increases myocardial functional recovery in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…27,28 In the myocardium of either S aureus-or LTA-treated rats, both TNF-␣ and IL-1␤ mRNA were found to be upregulated. 21,29 Like LPS, LTA has been shown to bind to CD14 and Toll-like receptors (TLRs) to induce activation of nuclear factor-B (NF-B), 30 -32 and cardiac expression of TLR2 was the prerequisite for cardiac depression associated with myocardial NF-B activation and TNF-␣ and IL-1␤ synthesis. 21 This may represent the prerequisite for the observation that LTA stimulates cytokine production and NO release in different cell types.…”
mentioning
confidence: 99%